Influence of PBL-Based LKPD with Wordwall on Fifth Graders’ Critical Thinking in Science (IJORER : International Journal of Recent Educational Research, 2026)
This study examines the influence of a Problem-Based Learning (PBL)–based Student Worksheet (LKPD) assisted by Wordwall media on the critical thinking skills of fifth-grade students in science learning, focusing on the aspects of focus, reason, and inference. Employing a quantitative approach with a quasi-experimental design, the research involved an experimental group using PBL-based LKPD with Wordwall and a control group receiving conventional instruction. Data were collected through tests, observations, interviews, and documentation, while instrument validation included expert judgment, Aiken’s V analysis, reliability testing, empirical validation, item difficulty, and discrimination analysis. The prerequisite normality and homogeneity tests indicated non-normal and non-homogeneous data, leading to the use of nonparametric statistical analyses. The Mann–Whitney test results showed significant differences between the experimental and control groups across all three aspects of critical thinking, with Asymp. Sig (2-tailed) = 0.000 < 0.05. N-Gain scores demonstrated high effectiveness in the experimental group (Focus = 96.70%, Reason = 87.90%, Inference = 79.30%), whereas the control group showed only moderate improvement. Correlation analysis using Spearman’s rank test further revealed very strong correlations among the Focus, Reason, and Inference dimensions. The findings conclude that the PBL-based LKPD assisted by Wordwall media is effective in improving students’ critical thinking skills and supports more engaging, interactive, and student-centered science learning in elementary classrooms.